Internalizing Character: A Phenomenological Study of Discipline, Independence, and Simplicity among Pesantren Students in Mandailing Natal - Asrin, Ahmad; Musa, Faisal (Eduprof : Islamic Education Journal, 2025)
This study delves into the lived experiences of students in Islamic boarding schools (pesantren) in Mandailing Natal to explore the internalization of discipline, independence, and simplicity. While pesantren are crucial for cultivating Islamic values, they face growing pressures from modernization and the erosion of local traditions. Employing a hermeneutic phenomenological approach, which emphasizes the interpretation of lived experiences to uncover deeper layers of meaning beyond descriptive accounts, this study seeks to understand not only what students experience but also how they make sense of those experiences within their cultural and spiritual contexts. Data were collected through in-depth interviews, participant observation, and document analysis. eyond these credibility strategies, the interpretative process followed three interrelated steps characteristic of hermeneutic phenomenology and IPA: reduction, thematization, and reflective interpretation of meaning. The findings demonstrate that character formation is a process of continuous habituation and integration with local wisdom. Discipline is cultivated through structured daily routines, independence is fostered by self-reliance, and simplicity emerges from communal living and a unique senior-junior mentoring system. This study argues that the pesantren system, through its reliance on practical engagement and local cultural practices, provides a powerful counter-narrative to the depersonalizing effects of globalization, shaping students' moral and spiritual resilience. The results offer specific insights for educators and policymakers on strengthening a form of character education that is both culturally rooted and contextually relevant for Indonesian students.